Penentuan Rute Kendaraan Heterogen Menggunakan Algoritma Insertion Heuristic - Saputra, Nanda; Sentia, Prima Denny; Andriansyah (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2018)
Distribution process at PT XYZ is identical to one of the variants of Vehicle Routing Problem (VRP) which there are several vehicles with different capacities and operation cost, called as Heterogeneous Fleet Vehicle Routing Problem (HFVRP). There are two kinds of vehicle that have been used, namely, vehicle As and vehicle Bs. Vehicle As has the higher operation cost than vehicle Bs. Currently, the company implements policies where vehicle Bs is used if all vehicle As have been used. This policy may lead the distribution cost is so expensive and its equal with the operation cost of vehicle As that also high. Routing aims to combine the use of available vehicles to generate minimal distribution costs in servicing the customers. This research uses mathematical model according to the description of the distribution system in the company. The model is verified and tested using the optimization software. Then the constraints of the verifiable mathematical model are used as the basis for developing Insertion Heuristic (IH) algorithm. Comparison of model solutions with developed algorithm solutions showed a difference of 11.6%. This implies that the algorithm generated solution is quite good as one of the heuristic approaches that result in optimal local solutions. Implementation of IH algorithm provides cost savings of 5.97% towards the actual distribution system in the company.